Rhabdomyosarcoma-Induced Uterine Inversion - Kin Li; Gavin Davis; Colleen Wittenberg; Alireza Abidi (Hindawi Limited, 2022)
Nonpuerperal uterine inversion is a rare clinical condition that involves prolapse of the uterine fundus into the uterine cavity and vaginal vault and possibly passed the introitus. The majority of these cases commonly involve benign tumors such as leiomyoma. However, another common cause of nonpuerperal uterine inversion is due to malignancies such as sarcomas. Rhabdomyosarcoma is a rare and aggressive malignancy of soft tissue cells that are common in children and rare in adults. One subtype called embryonal rhabdomyosarcoma is exceptionally rare. Therefore, report of embryonal rhabdomyosarcoma-induced uterine inversion is an exceedingly scarce and rarely documented clinical condition. In this case report, we present a rare case of a nulliparous 27-year-old female who presented with embryonal rhabdomyosarcoma-induced uterine inversion.